2005
DOI: 10.1073/pnas.0409177102
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcription factor KLF11 and its diabetes-associated gene variants in pancreatic beta cell function

Abstract: KLF11 (TIEG2) is a pancreas-enriched transcription factor that has elicited significant attention because of its role as negative regulator of exocrine cell growth in vitro and in vivo. However, its functional role in the endocrine pancreas remains to be established. Here, we report, for the first time, to our knowledge, the characterization of KLF11 as a glucose-inducible regulator of the insulin gene. A combination of random oligonucleotide binding, EMSA, luciferase reporter, and chromatin immunoprecipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
207
3
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(233 citation statements)
references
References 26 publications
5
207
3
11
Order By: Relevance
“…This opposing observation may be explainable by possible differences between native INS-1E beta cells used in our study and the INS832/13 beta cell line, which is derived from a highly selected INS-1 subclone stably transfected with a plasmid containing the human proinsulin gene [16]. More importantly, Neve et al [10] demonstrated activation of hInsP by cotransfected FLAG-tagged KLF11 in beta-TC3 beta cells. To be sure that this conflicting finding is not caused by the use of different beta cell lines, we confirmed the hKLF11-induced inhibition of cotransfected hInsP activity observed in INS-1E beta cells also in beta-TC3 beta cells.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…This opposing observation may be explainable by possible differences between native INS-1E beta cells used in our study and the INS832/13 beta cell line, which is derived from a highly selected INS-1 subclone stably transfected with a plasmid containing the human proinsulin gene [16]. More importantly, Neve et al [10] demonstrated activation of hInsP by cotransfected FLAG-tagged KLF11 in beta-TC3 beta cells. To be sure that this conflicting finding is not caused by the use of different beta cell lines, we confirmed the hKLF11-induced inhibition of cotransfected hInsP activity observed in INS-1E beta cells also in beta-TC3 beta cells.…”
Section: Discussionmentioning
confidence: 66%
“…Sequence analysis of hInsP not only retrieved the previously described GC box but also identified a CACCC box element, both putative binding sites of KLF11. Since our results are in contrast to those of Neve et al [10] and to better understand how hKLF11 regulates human insulin gene expression, we here further studied the functional role of the GC and CACCC box by electrophoretic mobility shift analysis (EMSA), mutation and 5′-deletion constructs of the hInsP in INS-1E and beta-TC3 beta cells.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations